KEBUDAYAAN SEBAGAI SUATU SINTESA EKONOMI ISLAM (Studi Antropologi Ekonomi Islam Pada Keraton Cirebon) - Yanuar Isyanto; Yanuar Isyanto; Karlina Karlina; Karlina Karlina (UIN Siber Syekh Nurjati Cirebon, 2023)
Humans are actually social beings who can always be relied on mutually between individuals and individuals, individuals with groups or groups. From this interaction humans create a habit or often called a